„THE SONG NOTEBOOK” APPLICATION - Kiščenko, Ilze; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
According historical facts the culture- national songs and dances- helped Latvians to remain the national identity through ruling of foreign power. Even up to now days these things, specially songs and singing, is very important way how to express the feelings. The slogan „people that sings” represents this Latvian feature. To promote singing the author of paper established a company „Dziesmu klade” (“Song notebook”) - the mobile application where users can make their own virtual song note book with lyrics and music. In this paper the author represents application’s software requirement specification to develop this business idea.